Network pharmacology and the experimental findings of Bushenhuoxue formula for improving hippocampal neuron injury in vascular demented rats - Shan Luo; Jiaxing Jing; Ying Zhang; Wentao Yu; Weijuan Gao (Journal of Integrative Neuroscience, 2021)
We used network pharmacology to predict the correlation between the pathway of Bushenhuoxue formula in the treatment of vascular dementia and carried out experiments to verify the correlation between drug composition and disease. By screening the active components and key targets through various databases and drawing the topological network diagram, we obtained 502 effective compound targets, 601 disease targets, 95 disease-related compound targets, and 162 pathways. The pathway related to vascular dementia may be neurodegeneration-multiple diseases, PI3K-Akt signaling pathway, Mitogen-activated protein kinase signaling pathway, or HIF-1 signaling pathway. By detecting the learning and memory ability of vascular dementia rats, the morphology of the hippocampus under the electron microscope, the degree of neuronal damage, and autophagy-related proteins, the results showed that the Bushenhuoxue formula could improve the neuronal injury induced by ischemia in the hippocampus, down-regulate the level of autophagy, and thereby improve learning and memory. Therefore, the Bushenhuoxue formula may improve the ischemic injury of neurons by regulating the mechanism of neuronal autophagy.